Design of an actively controlled steerable needle with tendon actuation and FBG-based shape sensing. Issue 6 (June 2015) - van de Berg, Nick J.; Dankelman, Jenny; van den Dobbelsteen, John J.
Highlights: We present the first actively (tip-)steered needle with integrated shape sensing. FBG-based shape feedback is used in a closed loop control approach. We present the first experimental validation study of this needle in a tissue phantom. The results provide insight in the mechanical system, its steering accuracy and precision. Abstract: This work presents a new steerable needle to facilitate active steering toward predefined target locations. It focuses on mechanical aspects and design choices in relation to the observed response in a tissue phantom. Tip steering with two rotational degrees of freedom was achieved by a tendon actuated ball joint mechanism. During insertion, the flexible cannula bends as a result of asymmetric tip–tissue interaction forces. The stylet was equipped with fiber Bragg gratings to measure the needle shape and tip position during use. A PI-controller was implemented to facilitate steering to predefined targets. During the validation study, nine targets were defined at a depth of 100 mm below the gelatin surface. One was located below the insertion point, the others at a radial offset of 30 mm in each of the eight principle steering directions. Per location, six repetitions were performed. The targeting accuracy was 6.2 ± 1.4 mm (mean ± std). The steering precision was 2.6 ± 1.1 mm. The ability to steer with this new needle steering approach is presented and the mechanical characteristics are discussed for this representative subset of steering directions.